Insurance as function-oriented element of system of economic safety of the country (Путеводитель предпринимателя)
In article questions and insurance problems from the economic point of view, country safety with minimization of insurance risks and ensuring property and insurance interests of objects and subjects of insurance are considered and analyzed.